A stepping stone approach to understanding harmful norms - Gulesci, Selim; Jindani, Sam; Ferrara, Eliana La; Smerdon, David; Sulaiman, Munshi; Young, Peyton (Centre for Economic Policy Research (CEPR), 2022)
This article was published in Centre for Economic Policy Research (CEPR) and the Article's website is at: https://cepr.org/active/publications/discussion_papers/dp.php?dpno=15776